Burnout and Turnover Intention Among Community and Hospital Pharmacists in Metro Manila, Philippines - Rogie Royce Carandang; Forter Puguon Jr.; Mary Louisse Santos; Elizabeth Ilagan; Kellie Gwyneth Gamboa; Jose Gerardo Aquino (Merits)
Burnout among pharmacists is an increasingly urgent concern, with previous studies emphasizing its physical, psychological, and occupational consequences. However, limited research has explored specific burnout experiences and their impact on turnover intentions among Filipino pharmacists. This study examined the association between burnout, its symptoms, and turnover intentions among pharmacists in Metro Manila, Philippines. We used the Burnout Assessment Tool and Turnover Intention Scale to conduct a cross-sectional study among 300 community and hospital pharmacists. A multiple logistic regression analysis examined the association between burnout and turnover intentions among pharmacists. Of the 300 pharmacists, 73.0% were at risk of or experiencing severe burnout, and 75.7% reported a turnover intention. Pharmacists at risk of or experiencing severe burnout showed a higher likelihood of leaving their jobs (Adjusted Odds Ratio [AOR] = 7.59; 95% Confidence Interval [CI] = 3.68, 15.64), especially if they felt exhausted (AOR = 2.49, 95% CI = 1.27, 4.89) or mentally distant (AOR = 3.92, 95% CI = 1.95, 7.86) from their work. Furthermore, dissatisfaction with salary, lack of incentives and promotions, and insufficient staffing emerged as other factors associated with the desire to leave. Addressing pharmacists’ physical and mental well-being, alongside workplace improvements, is crucial for reducing turnover intentions.